2020
DOI: 10.1021/acsami.0c05176
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Chlorine Resistance and Water Permeability during Forward Osmosis Separation Using Superhydrophilic Materials with Conjugated Systems

Abstract: Poor resistance to free chlorine severely impairs the service of conventional polyamide (PA) membrane in water treatment. Here we design a series of superhydrophilic aromatic sulfonate materials (ASMs) comprising successively increasing conjugated systems and ionizable groups (ASM-1, ASM-2, ASM-3) to develop a chlorine-resistant membrane via chemical modification. By altering the membrane physicochemical properties and surface structure, ASMs substantially improve the chlorine resistance and water permeability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Accordingly, the crosslinking network of the PA surface developed on the basis of chemical bonds and the internal hydrogen bonds was damaged, which deteriorated the selectivity of the membrane, resulting in a rise in the SRSF value. Similar results for the water flux and SRSF values were stated by Meng et al [ 79 ] and Song et al [ 58 ]. Thus, it was confirmed that the 0.050-B-GQD/PA TFNC membrane showed a much slower rate of PA layer damage while exposed to free chlorine and therefore possessed good chlorine resistance characteristics.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Accordingly, the crosslinking network of the PA surface developed on the basis of chemical bonds and the internal hydrogen bonds was damaged, which deteriorated the selectivity of the membrane, resulting in a rise in the SRSF value. Similar results for the water flux and SRSF values were stated by Meng et al [ 79 ] and Song et al [ 58 ]. Thus, it was confirmed that the 0.050-B-GQD/PA TFNC membrane showed a much slower rate of PA layer damage while exposed to free chlorine and therefore possessed good chlorine resistance characteristics.…”
Section: Resultssupporting
confidence: 90%
“…Due to its corrosive properties, a chlorine attack can cause significantly worsen membrane performance [ 77 , 78 ]. A chlorine attack is a critical challenge that could damage membrane integrity, reduce a membrane’s lifetime, or/and upsurge maintenance expenses [ 79 , 80 ]. In the current study, a 1000 ppm sodium hypochlorite solution was prepared using sodium hypochlorite (NaOCl) and DI water for the chlorine resistance analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Their FTIR spectra were collected and are shown in Figure b. In comparison with the original PEEK felt (PEEK-f), all of sulfonated felts had two new absorption peaks located at 960–1010 and 1038 cm –1 , which could be ascribed to vibrations of SO. The result proved that the pressed felts were successfully sulfonated.…”
Section: Results and Discussionmentioning
confidence: 94%
“…The triazine ring has a stable conjugated bond structure, which can improve the mechanical stability, thermal stability, and acid resistance of the NF membrane, , while sulfonated graphene and graphene oxide have long-term stability in alkaline solutions . Chlorine resistance of the NF membrane may be improved by applying aliphatic diamines as aqueous monomers, and melamine and aromatic sulfonate materials can also be used for preparing chlorine-resistant membranes. Constructing a sacrifice layer to preferentially react with oxidants mitigates the chlorination and hydrolysis of the PA NF membrane . Also, increasing membrane surface charge and hydrophilicity may reduce the adsorption of cleaning agents and their corresponding actions on the membranes, and improving the physical structure stability of the separation layer also can alleviate the compaction and pore swelling caused by chemical cleaning.…”
Section: Discussionmentioning
confidence: 99%